A Case study of persons in late adulthood living in retirement homes and their immediate family - Umali, Elloise Jhann M.; Jamero, Josephine Louise F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2020)
There is a rapid increase in the aging population and evidence of an increasing number of abandoned persons in late adulthood forcing them to live in retirement homes which is considered to be almost non-existent in the Philippines. The study aims to determine the knowledge and feelings of persons in late adulthood and their immediate family toward retirement homes. It also aims to identify the perspective of persons in late adulthood with regard to the presence and support received from families while in the retirement home and the perspective of their immediate with regard to the presence and support they are giving to their family members in late adulthood living in retirement homes. The subject of the study are the persons in late adulthood living in retirement homes and their immediate family. The research methodology is a case study, using a semi-structured one-on-one personal interview with the participants to gather data. Five qualified respondents for both sets of participants shall be interviewed. They must be persons in late adulthood living in a retirement home in Metro Manila, belonging in the middle-old age group of 75-84 years of age with a regularly visiting immediate family whose relationship does not necessarily have to be biological for as long as they visit the institution at least twice a month. Time and financial constraints are some of the limitations of the study and due to the COVID-19 pandemic, data gathering has been limited and made impossible.
Thesis Classification: F (Available for Public)
Thesis
Includes bibliographical references and appendices.
Keywords: Older people. -- Philippines; Retirement, Places of -- Philippines